Identification of Container Damage During Loading and Unloading on Full Geared Container Deck Vessels: USG Method - Binowo Ratunsee, Alpensam; Hasim Said, M.; Mulkan Azima, Ahmad; Sumali, Bambang (Dinasti International Journal of Management Science, 2024)
This study examines the factors that cause damage to containers during the loading and unloading process on full geared container deck ships with port destinations including Pasir Panjang Port (Singapore), Laem Chabang Port (Thailand), and Penang Port (Malaysia) and determines the priority problems that must be resolved immediately. This research uses mixed methods by combining quantitative and qualitative methods with an explanatory sequential design. The quantitative analysis used is the Urgency, Seriousness, and Growth (USG) method. Qualitative methods used observation, interviews, and documentation. The sample used is container damage on the MV. SS in the period August 2018 to August 2019. Causes of container damage during the loading and unloading process on the ship include the lack of supervision and concern of the crew for the security of containers during the loading and unloading process on the ship. From the results of USG method, it was found that container security activities were disrupted due to the duty crew participating in routine ship activities while at the port, even though the duty crew was fully responsible for reefer plug/unplug activities. Furthermore, there is no monitoring of the availability of loading and unloading equipment carried out by the crew so that the ship does not know the real number of lashing equipment on board.